On Station Evaluation of Thermo-stable Newcastle Disease Vaccine (Global Journal of Science Frontier Research, 2016)
Experimental study was conducted at Debrezeite Agricultural Research Center with proper experimental set up. Indigenous and koekeok chickens were used in four treatments and a control groups with three replications each. The replications were 12 local and 19 koekoek chickens. The four treatments use I2 vaccine through eye drop, water, parboiled barley and litter spray. Pre vaccination serum was collected at day 1, 14 and 20 while post vaccination was taken at day 36, 46 and at pre-challenge. Sample was also taken 8 days after the challenge with wild ND strain. Pathogenic Index HI and survival rate were used. The result shows, the antibody response and the pathogenic index was not significantly different between breeds but protection was higher in all treatments than the control. Chickens vaccinated with ocular and spraying has lower pathogenic index and higher survival rate than the rest. But for village system spray vaccination is recommended over ocular and others because it easy to administer, effective and can also be performed by trained farmers.
Keywords: I2; ND; vaccination; and chicken